Organizational factors as driver of salespeople customer-orientation behaviour: A look at Malaysian life insurance agents / Nor Azila Mohd Noor and Azli Muhamad - Mohd Noor, Nor Azila; Muhamad, Azli (Unit of Research, Development and Commercialization (URDC), UiTM Perlis & University Publication Centre (UPENA), 2006)
Customer-orientation behaviour, defined as a selling behaviour in which salespeople assist customers to satisfy their long-term wants and is undeniably important in today's selling environment. However, a complete understanding of the process and its antecedents is presently lacking and has received relatively little attention from marketers. This study seeks to identify the impact of three organizational-related factors on customer orientation behaviour, that is, the firm's degree of market-orientation, top management emphasis on customer-orientation, and a supportive work environment. Hypothesized relationships were tested using survey responses from a sample of 445 life insurance agents in Malaysia. The results suggest that top management emphasis positively influences insurance agents customer-orientation behaviour. It was also found that the firm's degree of market-orientation and customer-orientation behaviour is positively related. A supportive work environment was found to be unrelated to the adoption of customer-orientation behaviour. The results are compared with earlier findings and implications for further research are discussed